Karate kid : legends [videorecording (Blu-Ray)] - Lieber, Rob, 1976-; Cheng, Long, 1954-; Wang, Ben, 2000-; Jackson, Joshua, 1978-; Stanley, Sadie, 2001-; Ming-Na, 1963-; Oleff, Wyatt, 2003-; Knight, Aramis, 1999-; Macchio, Ralph, 1961- (Sony Pictures Home Entertainment, 2025)
After kung fu prodigy Li Fong relocates to New York City, he attracts unwanted attention from a local karate champion and embarks on a journey to enter the ultimate karate competition with the help of Mr. Han and Daniel LaRusso.